SISTEM INFORMASI GEOGRAFIS LETUSAN GUNUNG BERAPI KABUPATEN MAGELANG BERBASIS WEB - Mahasinul Akhlak, Muhammad Lutfi; Al Amin, Imam Husni; Gustiyargani, Alfian; Cahyo, Soliqin Nur; A.P, Arga Alundra (STMIK BINA PATRIA, 2024)
Indonesia is a country located in the Pacific Ring of Fire, which makes it prone to volcanic activity. One of the most famous active volcanoes is Mount Merapi, part of which is located in Magelang Regency. To reduce the impact of volcanic disasters, a systematic and data-based approach is needed. One of the most effective tools in disaster mitigation planning is the Geographic Information System (GIS). The purpose of this study is to build an interactive Web-based Geographic Information System for volcanic eruptions in Magelang Regency and to analyze the Risk, Hazard, Capacity, Vulnerability of Volcanic eruptions in each District in Magelang Regency. The research method used is an experimental method with a quantitative approach. Based on the calculation of User Acceptance Testing (UAT), users produced a value of 95.42% of the total 100%, which means that the system built has met the user-friendly criteria. The results of this study can be used for a WebGIS-based digital mapping prototype that can be used as a visualization tool for disaster zoning for volcanic eruption risk analysis in Magelang Regency.